2004
DOI: 10.1074/jbc.m311996200
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Growth Rate and ATP Concentration in Escherichia coli

Abstract: Previous studies showed that adenosine triphosphate (ATP) concentrations in Escherichia coli changed during certain growth transitions and directly controlled the rate of rRNA transcription initiation at those times. The relationship between ATP concentration and rRNA transcription during steady-state growth is less clear, however. This is because two commonly employed methods for measuring ATP concentrations in bacteria, both of which rely on physical extraction followed by chromatographic separation of small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
133
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 23 publications
17
133
1
Order By: Relevance
“…Having grown the cells under what they termed 'moisture stress', they found that cell ATP content could be increased 2.2 fold by rewetting dry soils and that furthermore, the addition of glucose and ammonium salts increased ATP levels 5.9 and 2.8 fold respectively. Schneider and Gourse (2004) found that ATP levels in laboratory-grown E. coli remained constant with growth rate, and claimed that earlier work that had presented evidence of growth rate-related differences were in fact at fault due to the method used to extract ATP from the cells.…”
Section: Factors Affecting Intracellular Atp Contentmentioning
confidence: 99%
“…Having grown the cells under what they termed 'moisture stress', they found that cell ATP content could be increased 2.2 fold by rewetting dry soils and that furthermore, the addition of glucose and ammonium salts increased ATP levels 5.9 and 2.8 fold respectively. Schneider and Gourse (2004) found that ATP levels in laboratory-grown E. coli remained constant with growth rate, and claimed that earlier work that had presented evidence of growth rate-related differences were in fact at fault due to the method used to extract ATP from the cells.…”
Section: Factors Affecting Intracellular Atp Contentmentioning
confidence: 99%
“…A standing controversy regarding the reliability of methods of NTP extraction was resolved in favor of the formic acid extraction method on the basis of a newly developed luciferasebased bioassay to measure available ATP pools (60). Using the formic acid extraction method, we observed a substantial increase in all four NTPs during outgrowth of E. coli from sta- lanes 1 and 2), 90 (lanes 3 and 4), 120 (lanes 5 and 6), 150 (lanes 7 and 8), and 390 min (lanes 9 -12).…”
Section: Discussionmentioning
confidence: 99%
“…The ATP levels of the complemented strain C0972 and the wild-type strain 8004 were almost identical ( Table 2), indicating that the ATP production of the mutant could be restored completely by the wild-type gapA gene in trans. The intracellular ATP levels of the Xcc strains were also determined by the method described by Schneider & Gourse (2004). The result also displayed that the gapA mutant produced significantly less intracellular ATP than the wild-type (Table 2).…”
Section: Gapdh Affects the Intracellular Atp Level Of Xccmentioning
confidence: 99%
“…Standard ATP curves were generated with standards containing known amounts of ATP in Tris/EDTA buffer. Intracellular ATP levels were also measured by the modified method developed by Schneider & Gourse (2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation